Children Victims of The Justice System in Nepal with Reference to The Applicability of Forensic Psychology - Bakhadyo, Laxmi (Kathmandu School of Law Review, 2021)
The motto of the justice system is to provide justice to victims. A question frequently raised is whether it is ‘criminal justice system’ or ‘victim justice system’. While it was supposed to be justice system in totality, children victims of sexual abuse were found to be victimized when they encountered the justice mechanism in Nepal. It was found that the ratio of children being victimized by acquaintances is significant. Similarly, data reveals that the number of female victims is much higher than male victims. Children victims of sexual violence are prone to psychological problems, and they might suffer from such problems in their adulthood as well. Justice system and court proceedings in Nepal are focused on perpetrators and their rights whereas victims are treated a means to collect evidence and prove offense. Child victims of sexual abuse are to be treated with special care and the person questioning him/her ought to be aware of their psychological state. In practice however, this has not been followed. Giving compensation to victim has been regarded as being equivalent to justice. Application of psychology is very rare in the investigation process and in the judicial system; with regards to victims, it is almost equal to null. The overall practice is focused on crime, criminals and conviction rather than on victims and their justice.